Electoral studies: Understanding some research problems - Idid, Syed Arabi (Penerbit UKM, 2017)
This paper discusses the problems researchers experience in conducting electoral research. One approach researchers use in conducting electoral studies is quantitative with the use of empirical data while another approach would be qualitative. Researchers show preference for mixed methods, incorporating both the quantitative and qualitative approaches as the research areas have become more complex. A proper method selection is required and the nature of the research problem identified. The methods used would depend on the objective of the study, the resources and the expertise available. One research area using quantitative research is Agenda Setting that used survey and content analysis. Agenda setting studies the effects of the media on public opinion to explain for political behaviour. Public opinion would require the use of survey as a form of methodology to seek what people perceive of current issues and what issues were deemed important when making voting decisions. Using scales in conducting longitudinal research would obtain a more meaningful perspective.